1991
DOI: 10.1161/01.str.22.9.1117
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and hemodynamic aspects of low-flow infarcts.

Abstract: We used single-photon emission computed tomography to measure cerebral blood flow, cerebral blood volume, and cerebral perfusion reserve and transcranial Doppler sonography with CO, stimulation to assess hemispheric vasomotor reactivity in 37 patients and in normal controls. Computed tomography and magnetic resonance imaging were performed to differentiate morphologically low-flow infarcts (n=17) from territorial infarcts (n=20). In patients with either type of infarct, blood flow was decreased and blood volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
0
7

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 27 publications
7
76
0
7
Order By: Relevance
“…40 However, in patients with ICA occlusion and contralateral ICA stenosis, cerebral hemodynamics may be more disturbed, and higher risks of ischemic stroke have been reported for both symptomatic and asymptomatic patients. 2,3,41,42 A number of studies have shown that contralateral CEA in patients with ICA occlusion has a long-term effect on prevention of stroke on the side of endarterectomy and on the side of ICA occlusion, which is explained by improvement of cerebral hemodynamics on the side of ICA occlusion; however, among these studies, only the NASCET study was a randomized trial. 5,6,41,43,44 After CAS, a similar improvement was seen in our patients and in previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 However, in patients with ICA occlusion and contralateral ICA stenosis, cerebral hemodynamics may be more disturbed, and higher risks of ischemic stroke have been reported for both symptomatic and asymptomatic patients. 2,3,41,42 A number of studies have shown that contralateral CEA in patients with ICA occlusion has a long-term effect on prevention of stroke on the side of endarterectomy and on the side of ICA occlusion, which is explained by improvement of cerebral hemodynamics on the side of ICA occlusion; however, among these studies, only the NASCET study was a randomized trial. 5,6,41,43,44 After CAS, a similar improvement was seen in our patients and in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…1 Severe stenosis in contralateral ICA occlusion may further impair cerebral hemodynamics and increase the risk of cerebral ischemic attack. 2,3 CEA of the carotid stenosis is often performed in such patients, and this procedure may have hemodynamic benefits. [4][5][6] However, CEA for patients with contralateral ICA occlusion also has a high surgical risk.…”
mentioning
confidence: 99%
“…16 Decrease in CBF has been implicated in the pathogenesis of neurodegenerative disorders such as dementia and certain cerebrovascular events such as low-flow infarcts. 17,18 A recent study showed that lower total CBF is an independent risk factor for mortality and adverse clinical outcomes in patients with heart failure. 19 However, little is known about the independent role of CBF in the maintenance of health and survival in older people.…”
Section: Resultsmentioning
confidence: 99%
“…Fuchs et al (2002) showed that stroke after PCI affects mainly elderly patient with risk factors for atherosclerosis. Cerebral hemodynamic impairment in these patients would increase the risk of ischemic disease secondary to reduced flow (Weiller et al, 1991;Miyazava et al, 2001), which may be additionally compromised by systemic hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%